2007
DOI: 10.5670/oceanog.2007.84
|View full text |Cite
|
Sign up to set email alerts
|

Ridge-Hotspot Interactions: What Mid-Ocean Ridges Tell Us About Deep Earth Processes

Abstract: Hawaii (Morgan, 1971). In contrast, the "anti-plume" school argues that many of the observed "hotspot" volcanic and geochemical anomalies are simply due to melts leaking through tensional cracks in Earth's lithospheric plates-in other words, hotspots reflect only where the lithospheric plate is cracked, allowing melts to pass through, and not where the underlying mantle is hotter (see www.mantleplumes.org). A hybrid notion is that only a relatively small number of hotspots, especially those of enormous magmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 22 publications
2
39
0
Order By: Relevance
“…Previous studies indicated that the frequency of hydrothermal activity on MORs has a strong linear relationship to spreading rate, a proxy for the long-term magma budget, but that this relationship does not appear to hold on hotspot-affected ridge segments (Dyment et al, 2007;, Baker et al, 2008b). The most recent prior compilation of systematic hydrothermal surveys (Baker and German, 2004) presented a linear equation for this relationship, which was revised slightly , based on 12 non-hotspot surveyed portions of MORs totaling 9% of the global ridge strike length.…”
Section: Predicting the Number Of Undiscovered Vent Fields On Spreadimentioning
confidence: 97%
“…Previous studies indicated that the frequency of hydrothermal activity on MORs has a strong linear relationship to spreading rate, a proxy for the long-term magma budget, but that this relationship does not appear to hold on hotspot-affected ridge segments (Dyment et al, 2007;, Baker et al, 2008b). The most recent prior compilation of systematic hydrothermal surveys (Baker and German, 2004) presented a linear equation for this relationship, which was revised slightly , based on 12 non-hotspot surveyed portions of MORs totaling 9% of the global ridge strike length.…”
Section: Predicting the Number Of Undiscovered Vent Fields On Spreadimentioning
confidence: 97%
“…east-west volcanic lineament formed between 7 and 10 Ma (Dyment et al 2007). The Rodrigues Ridge has been proposed to result from a ridge-hotspot interaction (Morgan 1978) and could represent the surface expression of a channelled asthenospheric flow connecting La Réunion hotspot and the ridge axis, on which one retrieves geochemical signatures from La Réunion hotspot (e.g.…”
Section: Lithospheric Structure Beneath La Réunion Hotspot Track 109mentioning
confidence: 99%
“…1). This relative dense coverage was extended eastward to the Central Indian Ridge, in order to investigate hypothesized asthenospheric flow from hotspot to ridge (Morgan, 1978;Dyment et al, 2007). The seismicity in the reliably active South Sandwich subduction zone generates body-wave paths which sample the mantle beneath La Réunion at greater depths.…”
Section: The Obs Networkmentioning
confidence: 99%